Engaging Students‘ Speaking Skill Using Role Play in Junior High School - Kamal Yusuf; Feby Anggita Setyamardani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This paper aimed to investigate to what extent the role play technique, especially semi-scripted could improve students’ speaking skill in English. This research was a descriptive qualitative in nature where was conducted at SMP Rahmat in Surabaya, East Java. Thirty students participated in this study and they have practiced a semi-scripted role play as one kind of role play techniques. There was pre-test and post-test applied, before and after the role play activities. The tests were done to measure students’ speaking skill. The results of this study showed that semi-scripted role play technique could significantly improve and affect properly the speaking ability of the students. Furthermore, by employing the semi-scripted role play, the students could freely express their feelings and make them able to explore their creativity in more ways to enable them facing the real life. Keywords: Role Play, Dialogue, Speaking Skill, English Teaching